An experimental study of turbulent heat transfer separation external in an annular passage - Hussein, Togun; Hakim, S. Sultan; Irfan Anjum; Kazi, S.N. (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.